Association between postpartum depression and partner support in a maternal childhood center from Lima - Ramos Cárdenas, Mayra Alejandra (2022)
Objective. To determine the association between partner support and postpartum depression in women from a maternal and child center in Lima, 2020. Material and methods. Descriptive correlational cross-sectional study. The sample consisted of 122 women who met the inclusion and exclusion criteria in whom the Edinburgh Scale and the Partner Support Scale were applied. Spearman's Rho Correlation coefficient was used in the inferential statistical analysis. Results. 20.5% of women presented postpartum depression (PPD). The correlation of the dimensions of partner support with PPD was: emotional support (Rho = -0.464), instrumental support (Rho = -0.402) and informational support (Rho = -0.388), therefore, an inverse correlation was demonstrated and moderate in each dimension. Conclution. Partner support is inversely related to postpartum depression in women. Therefore, the participation of the couple in the postpartum period could reduce the chances of developing this pathology within the first year postpartum.